Student Participation in the Activities of the Department's Student Association (HMJ) is Connected with Learning Achievements in the Department of Mechanical Engineering Education, Manado State University - Tamba, I. Parsaoran (JR Education, 2022)
The purpose of this study is to determine the relationship between student participation in the activities of the Department Student Association (MHJ) and Student Learning Achievement. The object of research was students of the Department of Mechanical Engineering Education with a total sample of 65 students. The statistics used are non-parametric statistics with analysis using Chi Squared. The results of the analysis showed that there was no relationship between student participation in HMJ activities and the learning achievements achieved by students with the proven calculation results which showed that the chi squared count was smaller than the chi squared table (χ2calculate = 0.764 < χ2table = 9.94). The conclusion is that students can participate in all HMJ activities while running lectures to get good or excellent learning achievements. Keywords: Participation, Department Student Association (MHJ), Learning Achievement